Evaluation of the Efficiency of Microfinance Institutions in Mexico. An Analysis through the Data Envelope to Social Banking - Ortiz Zavala, Alberto; Kido Cruz, Antonio; Kido Cruz, María Teresa; Razo Villagómez, Cesar Augusto; Granados Gómez, Juan Paulo (Unidad Editorial UPTC, 2023)
The present investigation has the objective of evaluating the efficiency in the microfinance institutions in the 32 Mexican Federative Entities, in order to know which are the most efficient institutions and relate it to the institution's corporate purpose. The Data Envelopment Analysis (DEA) methodology is used, both the Charnes, Cooper and Rhodes method, the Banker, Charnes and Cooper method and the Sexton Crossed Efficiency Method. As a limitation, there is the fact that the most current data found is from the year 2020. As a result, it is observed that the average efficiency of the MFIs is located at 0.60885551 for the 32 federal entities, pointing to Mexico City at the top as the most efficient. Also, the research finds that the institutions that pursue an economic purpose are the ones that achieve greater efficiency, while the institutions that seek a social objective present the lowest one. Since a sector of the population does not have access to traditional banking the article is relevant; the contribution is in the study of social banking from the microfinance sector. JEL Codes: C14 Received: 18/02/2023.  Accepted: 28/04/2023.  Published: 26/05/2023.